How does corporate taxation affect business investment? Evidence from aggregate and firm-level data - Hanappi, Tibor (OECD Publishing, 2023)
Business investment in OECD countries has remained weak, in particular since the 2008 global financial crisis. At the same time, the cost of capital has significantly and steadily decreased over the last thirty years, reflecting a fall in both interest rates and corporate tax rates. This raises the question of whether business investment still responds to the cost of capital and thus whether corporate tax policy can support investment. This paper analyses trends in business investment and in the cost of capital in OECD countries over the past three decades. Then, it investigates empirically the sensitivity of business investment to corporate taxation, and how this sensitivity varies across firm, investment and tax-design characteristics. Panel regressions at the firm and industry levels confirm that business investment rates are negatively related to corporate taxation, measured by country-level forward-looking effective tax rates. However, the tax sensitivity of business investment has fallen significantly since the global financial crisis. It also differs significantly across firms, assets, and corporate tax design characteristics. Overall, the estimation results suggest that a nuanced and granular approach to corporate tax policy, accounting for heterogeneity in tax sensitivity, is needed to support investment effectively. The paper discusses possible policy options, including the reduction of non-profit taxes, the use of targeted corporate income tax instruments, and the use of more generous capital allowances where they may induce strong investment responses
Keywords: Taxation; Economics